Analisis Tindak Tutur Ilokusi pada Interaksi Penjual Pembeli Live TikTok Kajian (Pragmatik Searle) - Cindy Irene Githa Sihombing (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
Language plays a crucial role in human communication. Technological advancements, such as the Internet and cell phones, have revolutionized long-distance communication. The Internet on mobile phones has created unique communication forms, including online shopping on platforms like TikTok. This enables easy shopping from anywhere with internet access and payment via ATM. Interactions between buyers and sellers in online shopping involve various linguistic acts, facilitating transactions between strangers. This research explores (1) forms of speech acts in seller-buyer interactions on TikTok Live, (2) strategies of these speech acts, and (3) the functions of speech acts in these interactions. Using qualitative descriptive research, the study analyzes audio segments from conversations in women's equipment transactions on TikTok. Data collection was done through documentation, and analysis involved data reduction, presentation, and conclusion drawing. Results show differences in speech act forms, strategies, and functions. Future research is suggested to delve deeper into these aspects, using this study as a reference for broader investigations.